PHILOSOPHY OF ISLAMIC EDUCATION ACCORDING TO SYED MUHAMMAD NAQUIB AL-ATTAS - Usiono, Usiono (Proceeding International Seminar of Islamic Studies, 2023)
The emergence of the Renaissance provided a spirit of change for Western civilization, marked by various kinds of discoveries by Western scientists. However, there is one side that should be of particular concern to Muslim scientists named Syed Muhammad Naquib al-Attas, where the spirit of renaissance has its own impact on Muslims, especially Islamic education, namely the separation between Islam and Science. Religion goes its own way, as does science, so science is seen as value-free. This paradigm is part of the study of the philosophy of Islamic education, which examines and discusses critically everything about Islamic education. The method used in this study uses Library Research or what is known as a literature study, which is a study that uses literature references, namely journals, books, and so on. Syed Muhammad Naquib al-Attas believes that Islamic education that takes place today must be criticized from all aspects, one of which is by redefining Islamic education, because the definition that is currently understood has been mixed with the understanding brought by Western civilization. Education for him cannot be termed Tarbiyah but is more appropriate with ta'dib because this definition will guide Muslims to become Insan Adabi, namely individuals whose movements, steps in life are based on the principles of Islamic teachings.